Effect of High-Pressure Processing and Long-Time Storage on Color, Lipid Oxidation, and Free Amino Acids Profile of Beef - Marta Chmiel; Olga Świder; Marek Roszko; Lech Adamczak; Aneta Cegiełka; Dorota Pietrzak; Tomasz Florowski; Marcin Bryła; Anna Florowska (Applied Sciences, 2025)
This study aimed to evaluate the effect of high-pressure processing (HPP, 300, 400, or 500 MPa, 5 min, 5 °C) on the color, lipid oxidation, and free amino acids profile of skin-packed beef stored under cooling conditions (0–4 °C) for 56 days. The pH of the HPP-treated beef (500 MPa) was stable during storage (5.6–5.7) and significantly higher (p = 0.0010) than that of the control meat at the end of the storage time. During storage, the pH of the control meat decreased up to 5.3 on day 56. The HPP, especially 500 MPa, triggered faster lipid oxidation, leading to higher TBARS (thiobarbituric acid reactive substance) index values than the control meat (1.9 vs. 0.6 mg MAD/ kg of product at the end of storage time). Also, the extension of the storage time resulted in an increase in the TBARS index values of beef, which was greater when higher pressures were used. Moreover, HPP significantly modified the free amino acids profile of the meat. The use of HPP reduced the content of most of the free amino acids analyzed (except leucine, phenylalanine, and lysine) compared to the control meat, and the exposure to higher pressures resulted in greater losses (even a 2–3-fold lower content at the end of storage time). Furthermore, the dynamics of the increase in the free amino acids content during beef storage were higher for the control and HPP300 and lower for HPP400 and HPP500 meat. It seems that knowledge of lipid oxidation, color changes, and the content of free amino acids in beef, especially those constituting biogenic amine precursors, may help optimize process parameters such as pressure and beef storage time, to minimize undesirable quality changes. Considering the high costs of HPP, it seems also necessary to conduct a sensory evaluation to assess its potential usefulness in extending the shelf-life of culinary beef. Additionally, the changes occurring in beef within the first few hours after HPP treatment also need further investigation.